2018
DOI: 10.1177/0266242617751596
|View full text |Cite
|
Sign up to set email alerts
|

Emotional paths leading to opportunity desirability and feasibility beliefs through controllability

Abstract: Extant studies promote opportunity belief as an antecedent of entrepreneurial action. However, we do not sufficiently understand how beliefs about the desirability and feasibility of an entrepreneurial opportunity are formed. We argue that desirability and feasibility are related but distinct micro-foundations of entrepreneurial action formed through different cognitive-emotional mechanisms. Drawing on the appraisal tendency framework, we investigate the indirect effects of three basic emotions (anger, fear an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 133 publications
(240 reference statements)
3
36
0
Order By: Relevance
“…With this finding, we further our knowledge about opportunity evaluation and contribute to the appraisal theory in entrepreneurship (e.g. Foo, 2011;Podoynitsyna, van der Bij, & Song, 2012;Welpe et al, 2012) by extending previous research that has shown how appraisals emerge based on discrete emotions in the start-up process (Ivanova, Treffers, & Langerak, 2018); our study shows that evaluations of an opportunity can also emerge when different types of emotional information are provided and by showing how they influence venture goal commitment. In addition, this finding relates to Lazarus appraisal theory (Lazarus, Kanner, & Folkman, 1980) that states that the evaluation of an objectin this case the venture opportunityis only informed by appraisals if the given information is of compelling personal value.…”
Section: Implications For Researchsupporting
confidence: 75%
See 1 more Smart Citation
“…With this finding, we further our knowledge about opportunity evaluation and contribute to the appraisal theory in entrepreneurship (e.g. Foo, 2011;Podoynitsyna, van der Bij, & Song, 2012;Welpe et al, 2012) by extending previous research that has shown how appraisals emerge based on discrete emotions in the start-up process (Ivanova, Treffers, & Langerak, 2018); our study shows that evaluations of an opportunity can also emerge when different types of emotional information are provided and by showing how they influence venture goal commitment. In addition, this finding relates to Lazarus appraisal theory (Lazarus, Kanner, & Folkman, 1980) that states that the evaluation of an objectin this case the venture opportunityis only informed by appraisals if the given information is of compelling personal value.…”
Section: Implications For Researchsupporting
confidence: 75%
“…This argument is based on appraisal theory, which states that people's cognitive appraisals of situations generate specific emotional responses which can affect judgement, decision making, and behaviour (Lerner & Keltner, 2000;Smith & Ellsworth, 1985;Tiedens & Linton, 2001). Extant entrepreneurship research has already built on appraisal theories showing that emotions and cognitive appraisals can influence opportunity desirability and feasibility beliefs as micro-foundations of entrepreneurial action (Ivanova, Treffers, & Langerak, 2018), opportunity evaluation and exploitation (Welpe et al 2012), risk preferences (Foo, 2011;Podoynitsyna, Van der Bij, & Song, 2012).…”
Section: Opportunity Evaluation As Mediator In the Relationship Betwementioning
confidence: 99%
“…Krueger et al argue that higher levels of self-efficacy increase perceptions of venture feasibility, thus fostering entrepreneurial behavior [38]. In this paper, ESE is defined as entrepreneurs' self-efficacy in accomplishing value creation [22,24].…”
Section: Opportunity Confidencementioning
confidence: 97%
“…Nevertheless, perceived desirability should be domain specific in order to be equivalent to attitude toward action [4,50]. The entrepreneur's attitude toward value creation (AVC) or opportunity desirability [22,24] is the conviction that offering the new product, service, or venture is the right course of action [54]. The theory of planned behavior [55] holds that because attitude toward action is important predictor of intention, it might also increase the motivation to obtain practical market knowledge prior to action.…”
Section: Opportunity Confidencementioning
confidence: 99%
See 1 more Smart Citation